Manajemen Pendidikan Agama Islam Pra Sekolah untuk Menguatkan Nilai-Nilai Keislaman Anak Usia Dini - Mutia Bustamam (Yayasan Madinah Al-Aziziyah, 2026)
Islamic religious education at the preschool level plays an essential role in developing children’s faith, moral character, worship habits, and social behavior from an early age. However, its implementation in some educational institutions remains limited to routine religious activities that are not systematically, integratively, and sustainably managed. This study aims to analyze the management of preschool Islamic religious education and explain its role in strengthening Islamic values among young children. The study employed a descriptive qualitative library research method. Data were obtained from books, journal articles, research reports, and scholarly documents related to educational management, Islamic religious education, preschool education, and children’s religious development. The data were collected through documentation and analyzed using content analysis involving selection, classification, comparison, interpretation, and conclusion drawing. The findings indicate that strengthening Islamic values requires the integrated implementation of planning, organizing, actuating, supervising, and evaluating functions. Islamic education programs become more effective when delivered through exemplary behavior, habituation, Islamic stories, educational games, simple worship practices, and direct experiences appropriate to children’s developmental stages. The involvement of school principals, teachers, parents, and the surrounding environment also determines the continuity of religious habituation between school and home. This study concludes that preschool Islamic religious education should not merely be implemented as a series of routine activities but should be managed systematically, collaboratively, contextually, and continuously. The study contributes to the field by offering a conceptual framework for managing preschool Islamic religious education that emphasizes the development of children’s Islamic behavior and daily religious habits.